Ambiente virtual colaborativo para apoio ao ensino de circuitos integrados baseado em equipe - Prevedello, Peter (2018)
This paper describes the design and development of a virtual collaborative environment to support team-based education of integrated circuits design, named IC-COLLAB, and its implementation within the Grupo de Microeletrônica (GMICRO) of Universidade Federal de Santa Maria (UFSM). Through a simple web interface, the collaborative virtual environment provides collaborative tools that ensure project organization and efficient cooperation among participants, enhancing individual practices, teamwork, and leadership through coordination and communication. A hierarchically organized repository allows to save and share libraries developed individually by students. A version controller enables all participants to manage and document the changes made in the libraries. Communication tools allow the exchange of ideas and knowledge during the activities. Sharing of supporting materials and project suggestions can be done at any time. Finally, whenever necessary, the environment allows the coordinator to compile a given project, executing the copy of all the libraries to a particular repository where it can be shared for all the users of the environment and used in another project. As case studies, two integrated circuits were developed, which have demonstrated that the proposed virtual environment enhances the organization, safety, documentation and quality of the projects.